Emphysematous Cystitis Found Incidentally in a Patient Undergoing Hip Arthroplasty: A Case Report. Issue 3 (July 2015) - Kim, Sang-Rim; Dimitriou, Dimitris; Nam, Uk; Park, Yong-Geun; Choi, Sung-Wook; Seo, Kyu-Bum; Kim, Hee Joong; Nam, Kwang Woo
Abstract : Case: Emphysematous cystitis is a rare, complicated urinary tract infection that is potentially life-threatening if left untreated. We present the case of an eighty-one-year-old woman with left hip pain from a low-energy fall with no associated urinary symptoms. Pelvic computed tomography revealed a left femoral neck fracture and an air-fluid level in the bladder. Bipolar hemiarthroplasty was delayed for three weeks to allow for the potentially serious urinary tract infection to resolve. Conclusion: Increased awareness is required for early diagnosis and treatment of asymptomatic emphysematous cystitis in a patient presenting with musculoskeletal symptoms.